THE IMPACT OF MODERNISM ON UZBEK LITERARY WORKS - Sevaraxon Jabaraliyeva Nozimjon kizi, Nargiza Toirova Isaqovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Special attention is paid to the issue of character creation in world literature, and there is a need to reveal the psychological foundations and factors of artistic character creation. After all, a work of art cannot be perfectly imagined without an artistic character and its psychological foundations. That is why in literature, especially in Uzbek literature, it is of scientific-theoretical importance to study, analyze and draw conclusions about the works of writers in the form of examples. Therefore, a mature work of art is considered important as an expression of the change and evolution of people's consciousness, thinking.